Capacitated Vehicle Routing Problem In Optimization Of Waste Truck Routes Using The Particle Swarm Optimization Algorithm - Rambe, Siti Rahmi; Rakhmawati, Fibri (Politeknik Ganesha Medan, 2023)
In this research process, the aim is to determine the shortest route for transporting waste with the shortest or minimum total distance. In this case, what must be considered is the transportation of waste, regarding the distance between the location of the waste source to the landfills. The problem of waste transportation routes can be made in a mathematical method. The method used in waste transportation is the Capacitated Vehicle Routing Problem (CVRP) method. In solving the problem of transporting waste using the CVRP method, distance must be minimized or optimized using the Particle Swarm Optimization Algorithm. On the initial route of work area 1 there is the o-p-q-r-s-o route which has a total distance of 133.5 Km, in which there are several villages such as the Mambang Muda TPA - Belungihit Village - Aek Hitetoras Village - Brussel Plantation Village - Aek Tapa Village - Mambang Muda TPA. And after the latest garbage transportation route uses the PSO algorithm, the optimal distance is 132.5 Km with the o-s-q-r-p-o route where the village is Mambang Muda TPA - Aek Tapa Village - Aek Hitetoras Village - Brussels Plantation Village - Belungihit Village - Mambang Muda Landfill. In WK 2 there is an initial route o-p-q-r-s-o which has a total distance of 153.9 Km, in which the route has several TPA Mambang Muda villages - Marbau Village - Lobu Rampah Village - Simpang 4 Village - Pernantian Plantation Village - Mambang Muda TPA. And after the latest garbage transportation route uses the PSO algorithm, the optimal distance and route is 127.7 Km. In work area 3 with the initial route and distance of 150 and after using the PSO algorithm, the optimal route and distance is 137.1 Km. In work area 4 with a route and distance of 127.8 Km, the optimal route and distance using the PSO algorithm is 149.8 Km. Work area 4 has a route and initial distance of 157.8 Km and the optimal PSO route and distance is 149.8. The 5th working area has an initial distance of 180.3 and the PSO route is 134.3 Km. The working area of ​​the 5 initial routes is 152.4 Km and the PSO route is 152.4.